Criminalizing Corporations In Environmental Crimes : Memidanakan Korporasi Dalam Kejahatan Lingkungan Hidup - Agustian, Sanggup Leonard; Sugianto, Fajar; Michael, Tomy (Rechtsidee, 2020)
The research objective is to find out how criminal law against the environment accommodates criminal acts committed by corporations and to find out the practice of settlement through criminal law instruments in terms of corporate criminal liability in the environmental sector. The research method used is a normative juridical research method. There is the existence of criminal law as a part of 3 law enforcement regimes (state administrative law and civil law). then the involvement of criminal law in the settlement in the environmental sector regulates the existence of corporate criminal liability (business entity) as a subject of criminal law. The corporate criminal responsibility used by the UUPPLH is strict liability according to the law.